THE LINKAGE BETWEEN HEALTH AND FOOD SECURITY - Abdurahmonova Mastona Ravshan qizi (Bright Mind Publishing, 2025)
The basis of a healthy lifestyle depends on the use of high-quality and safe food products. Food safety ensures not only the sufficiency of products, but also their safety for human health. This article analyzes the relationship between food safety and human health. It also reviews the negative impact of poor-quality and contaminated food products on the human body, global statistics and ways to solve these problems.
Keywords: Food safety, health, poisoning, food infections, microbiological risk, quality control.